Dieter Schillinger explains about new and upcoming treatments for COVID-19 - Schillinger, Dieter (International Livestock Research Institute, 2021)
A presentation at the ILRI Townhall meeting on 3 December 2021 by Dieter Schillinger, Deputy Director General Biosciences.